Respostas
respondido por:
0
Temos que encontrar a razão:
r = 2a - a1
r = 7 - 4
r = 3
Razão = 3
========
an = ak + ( n - k ) * r
4 = 52 + ( 1 - k ) * 3
4 = 52 + 3 - 3k
4 = 55 - 3k
4 - 55 = -3k
-51 = -3k
-51 / -3 = k
k = 17
O termo é a17 = 52
===========
Prova:
an = ak + ( n - k ) *r
4 = a17 + ( 1 - 17 ) * 3
4 = a17 + (-16 ) * 3
4 = a17 - 48
4 + 48 = a17
a17 = 52
r = 2a - a1
r = 7 - 4
r = 3
Razão = 3
========
an = ak + ( n - k ) * r
4 = 52 + ( 1 - k ) * 3
4 = 52 + 3 - 3k
4 = 55 - 3k
4 - 55 = -3k
-51 = -3k
-51 / -3 = k
k = 17
O termo é a17 = 52
===========
Prova:
an = ak + ( n - k ) *r
4 = a17 + ( 1 - 17 ) * 3
4 = a17 + (-16 ) * 3
4 = a17 - 48
4 + 48 = a17
a17 = 52
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás